Critical Success Factors for enhancing the Building Information Modelling implementation in building projects in Singapore - Liao, Longhui; Teo, Evelyn Ai Lin (Journal of Civil Engineering and Management, 2017)
Although building information modelling (BIM) has been implemented in building projects in Singapore, barriers such as the duplicate efforts for designers and contractors to create models appear to exist. Thus, BIM implementation needs to be enhanced. The objectives are to identify the critical success factors (CSFs) for enhancing BIM implementation and investigate the interrelationships among these CSFs. 32 success factors were identified through a literature review and a questionnaire survey was conducted. The results indicated that 15 CSFs were identified and grouped into integration and accuracy of models (IAM), commitment and training from the management (CTM), and advantages and support of implementation (ASI) through factor analysis. The results from structural equation modelling (SEM) analysis revealed that CTM resulted in IAM and from ASI, while ASI facilitated IAM. The proposed framework indicating the CSFs and the intergroup relationships provides an in-depth understanding of BIM implementation and can help firms to commit on their part of project-wide BIM adoption and associated advantages. Overseas practitioners may use the identified success factors and follow the method to customise their own CSFs.